The Distribution of Zakat in an Effort to Improve the Welfare of Mustahik - Novian Putra Muhdila; Napiatun Mahmudah; Desi Isnaini; Herlina Yustati (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
The purpose of this research is to find out the BAZNAS program of Mukomuko Regency in the distribution of zakat funds for the welfare of mustahik ant to find out the improvement of mustahik welfare in Mukomuko Regency. This type of research is field study research. Data collection techniques using observation, interviews and documentation. Data analysis techniques with daya reduction, data presentation and Conclusion Drawin. Informants in the study amounted to 10 people. Based on the results of the study it was founds that BAZNAS Mukomuko has several programs including, Mukomuko Care, Mukomuko Religious, Mukomuko Healthy, Mukomuko Prosperous, Mukomuko Makmur, Mukomuko Smart. The improvement of mustahik welfare in Mukomuko city has not increased because there are still many mustahik who do not meet the mustahik welfare indicators.